EGO DAN POTENSI SOSIAL MANUSIA; REFLEKSI PEMIKIRAN MUHAMMAD IQBAL TERHADAP KONSEP JATI DIRI ALFRED NORTH WHITEHEAD - Ansori, Saiful; Azis Putra, Andri (Universitas Islam Negeri Imam Bonjol Padang, 2023)
Human existence is the main point for explaining all the conditions that have developed. Naturally, basic social issues cannot be separated from this discussion. This article attempts to review the essence of the human self, which is related to the social potential aspect. The article will use a hermeneutical-philosophical approach as the main analysis tool and human philosophy as the main component of the research. This research shows that the potential for human identity has a fairly close correlation with the concept of ego in Iqbal's philosophy. This relation contributed in social ways through human personality, basic identity, and uniqueness. All these conditions are aligned with Whitehead's organizational philosophy, which shows the importance of personal responsibility in optimizing identity.